Teaching bioethics: How to transmit knowledge, attitudes and values - León Correa, Francisco Javier (Acta Bioethica, 2008)
This work presents teaching experiences and reflections about how to teach bioethics in a manner that will fulfill three goals, and, at the same time, the challenges for the teacher: to offer knowledge from an interdisciplinary view about a scope of subjects becoming every day wider and more complex; to modify attitudes and behaviours and to influences on the health-patient professional relationship and on the models’ change in health care. The third goal consists on how to transmit the most appropriate ethic values for the healtch care professionals and for society in general. It also undertakes which values to communicate to students and how to carry it out, as well as how to evaluate in this discipline.